Comparison of i-gel, LMA-supreme, LMA-classic and LMAproseal as conduits of endotracheal intubation in newborns and infants: A manikin study - Ankay-Yılbaş, Aysun; Başaran, Betül; Üzümcügil, Filiz; Akça, Başak; İzgi, Murat; Canbay, Özgür (The Turkish Journal of Pediatrics, 2019)
Many types of supraglottic airway devices (SAD) including the traditional LMA (Laryngeal Mask Airway) are commonly used as conduits for intubation in pediatric patients with difficult airway. The aim of this study was to evaluate the feasibility of four types of commonly used neonatal and infant sized SADs as conduits of intubation. Fiberoptic-guided tracheal intubation with uncuffed, cuffed and armored uncuffed endotracheal tubes (ETT) sized between 2.5 and 4.5 through four commonly used types of size 1 and 1.5 SADs (i-gel, LMA-classic, LMA-supreme, LMA-proseal) were performed by two investigators on an infant manikin. The investigators scored two main outcomes with a 5-point scale: 1) passage of ETT during intubation through the SAD, and 2) passage of SAD over the ETT during SAD removal. The differences between the study groups were evaluated using the Bonferroniadjusted Mann-Whitney U test and p < 0.0083 was considered as statistically significant according to Bonferroni correction. i-gel sizes 1 and 1.5 both performed better as conduits for fiberoptic-guided intubation compared with LMA-proseal, LMA-classic and LMA-supreme with most of the uncuffed ETTs investigated (p < 0.0083). We found i-gel sizes 1 and 1.5 easily feasible to use even with uncuffed ETTs with an inner diameter of 3.5 mm and 4.5 mm, respectively. i-gel was the only SAD that was feasible for use as a conduit for armored ETTs. The passage of cuffed ETTs was problematic with all types of studied SADs. In conclusion; the choice of i-gel as a conduit for intubation could be safer than LMA-classic, LMA-supreme and LMA-proseal.
Keywords: difficult airway; infant; newborn; supraglottic airway device